Prototype design and implementing of a three-finger adaptive robotic gripper based on the FinRay® structure (2019)
Given the accelerated advancements in microelectronics and processing systems, robotics are constantly going forward in new areas alongside the industries. Some robotic handlers require being able to maneuver with objects with different dimensions, surfaces, and delicate textures, which sets the need for new final effectors with new mechanics and control features. Likewise, with the ongoing research developed in the bio-mimesis area, a very reliable and viable for replicating nature principles for the development of technological appliances. This document describes the mechanical design and the physical implementing process of an adaptive robotic gripper with jaws based on the FinRay® structure regarding the movement reaction of a fish fins. The achieved results show its effectivity and adaptability for the gripping of different objects.